ISLAMIC PENSION FUNDS PERFORMANCE IN TURKEY - Basak Turan Icke; Caner Akbaba (European Scientific Journal, ESJ, 2015)
Pension funds poses an important place in terms of increasing and encouraging savings for economies of countries. Accordingly, the private pension system in Turkey, which entered into force on 27 October 2003, has been still under development. Therefore, the performance of the pension funds has a considerable indicator characteristic for investors to utilize their savings with these investment instruments. Beside these, in Turkey, for spreading saving ability to all components of the society investors who have Islamic sensitiveness have been channelized into pension funds with new “helal” pension funds. In this study, performance of these pension funds operating in Turkey in the period of January 2013 and August 2015 will be measured by using regression analysis with explanatory benchmarks. For this purpose single and multi regression models will be employed. BIST 100, Government Debt Securities (GDS), and Gold Price Indices will be employed as explanatory variables for the single and multi regression models applied to pension funds.